Ionic Liquids – A New Era in Green Chemistry (International Journal of Engineering and Computer Science, 2017)
Green chemistry aims to provide environmentally benign products from sustainable resources, using processes that do not harm people or the environment. Most chemical reactions have been correlated in molecular solvents. Recently , have even, a new clan of solvents has emerged “ Ionic Liquids “.“. Ionic liquids (ILs) are new organic salts that exist as liquids at low temperature (